Pengaruh Transformasi Kebijakan Lingkungan terhadap Citra Negara Brasil pada Komunitas Global - Fienda, Tiara Elgi; Ansyari, Irvan; Widyanty, Resty (Department of Political Science - Universitas Sains Al-Qur’an, 2025)
The 2022 Brazilian presidential election drew widespread attention from both the Brazilian population and the international community, who hoped for a shift in policy that would support the protection of the Amazon rainforest. The election of Luiz Inacio Lula Da Silva as President launched a positive trend for the Brazilian government and fueled global optimism about the Amazon's future. The purpose of this study is to examine Brazil's environmental policy through the lens of strategic diplomacy, a descriptive qualitative approach to understanding a country's diplomacy in dealing with a complex global system (Prantl and Goh, 2016; and Doctor, 2023). The relationship between the Amazon rainforest's sustainability and Lula's election as President of Brazil will be addressed using three fundamental strategic diplomacy indicators: interconnectivity, nonlinearity, and emergence. This study regards Amazonian deforestation in Brazil as a problem that will not only destroy Brazil's natural environment, but will also threaten the survival of tropical forests as the world's lungs, as well as contribute to global temperature increases. The Amazon rainforest's importance is recognized internationally, not just in terms of the health of individuals living near the forest or in Brazil alone. This is a vital agenda for all leaders from various countries. In this way, in a nonlinear setting, a lack of support from various countries may compound the effects of deforestation in the Amazon rainforest. The subsequent domino effect would have global implications (emergence).